2019
DOI: 10.3390/beverages5040061
|View full text |Cite
|
Sign up to set email alerts
|

Sugary Kefir: Microbial Identification and Biotechnological Properties

Abstract: Background: The aim of the present study was to assess the microecosystem composition of three different fruit kefir grains used for the fermentation of apple juice (NAJ), cherry juice (SCN), and a solution of sugary water, enriched with plums (BSS). Methods: Yeast and bacterial populations were enumerated using classical microbiological techniques, clustered by RAPD-PCR genotyping, and identified by sequencing of the D1/D2 region of 26S-rRNA gene and the V1-V3 region of 16S-rRNA gene, respectively. The casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…However, the SDS-PAGE confirmed the proteolytic capacity for only three LAB strains. Similar results are often reported and may be attributed to insufficient incubation time [ 36 , 37 , 38 ]. Lancetti et al [ 34 ] have already reported the proteolytic capacity of Lcb.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the SDS-PAGE confirmed the proteolytic capacity for only three LAB strains. Similar results are often reported and may be attributed to insufficient incubation time [ 36 , 37 , 38 ]. Lancetti et al [ 34 ] have already reported the proteolytic capacity of Lcb.…”
Section: Discussionsupporting
confidence: 87%
“…Lipolysis has been extensively studied in fermented dairy, non-dairy and meat products [ 38 , 41 , 42 ]. Despite the fact that a certain level of lipolysis is a desirable attribute of microbial strains, in terms of synthesis of flavor precursors, only a few pieces of scientific literature have reported the microbial screening for lipolytic activity of sourdough microorganisms [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The applications of probiotic B. amyloliquefaciens plays a major role by producing essential nutrients and also making available the necessary breakdown of complex food components for better digestion. Moreover, the spore-forming B. amyloliquefaciens is resistant to low pH, varying temperatures, and other conditions which give it an advantage over sustaining at intestinal low pH gastric digestion and able to reach the small intestine. ,, In recent publications, the spore-forming B. amyloliquefaciens are being used for the probiotic products including yogurt, kefir, tempeh, kimchi, miso, pickles, natto, cheese, fermented cassava, and some fermented cereals …”
Section: Probiotic and Prebiotic Potentialsmentioning
confidence: 99%
“…There are two types of kefir, known as milk kefir (MK) and water kefir (WK) (Syrokou et al, 2019). The origin of MK was the Caucasian Mountain region (Sanli & Anli, 2020) and usually these are referred to as 'milk kefir grains'.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of MK was the Caucasian Mountain region (Sanli & Anli, 2020) and usually these are referred to as 'milk kefir grains'. Other names such as 'Kefer', 'Kippi', 'Kanphon' and 'Kiaphur' can be found in the literature (Unal et al, 2020). MK is traditionally made by fermentation of milk with MK grains (Sanli & Anli, 2020).…”
Section: Introductionmentioning
confidence: 99%